Association between maternal Group B Streptococcus surface-protein antibody concentrations and invasive disease in their infants. (2nd December 2015) - Dangor, Ziyaad; Kwatra, Gaurav; Izu, Alane; Adrian, Peter; Cutland, Clare L; Velaphi, Sithembiso; Ballot, Daynia; Reubenson, Gary; Zell, Elizabeth R; Lala, Sanjay G; Madhi, Shabir A
Abstract : Objectives: Group B Streptococcus (GBS) surface-proteins have been shown to be immunogenic and potential vaccine candidates. We aim to determine the association between maternal IgG antibodies to select GBS surface-proteins and invasive GBS disease in their infants. Methods: Using a matched case–control study, maternal antibody levels for GBS-immunogenic bacterial adhesin, fibrinogen-binding protein A and pilus-island (PI) PI-1, PI-2a, PI-2b were compared between infants with invasive GBS disease and well-baby controls. Results: The absolute risk of disease did not differ between cases and colonized controls with increasing antibody concentrations for these surface-proteins. There was, however, a relative risk reduction in invasive disease associated with fibrinogen-binding protein A, with an adjusted odds ratio of 0.04 (95% CI: 0.01–0.69) at antibody levels ≥10, 000 AU/ml. Conclusion: We have not demonstrated an association between naturally occurring fibrinogen-binding protein A, GBS-immunogenic bacterial adhesin, and PI surface-protein antibodies and the risk of invasive disease in young infants. These surface-proteins may not be suitable GBS vaccine candidates.